2020
DOI: 10.29333/iji.2020.13139a
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Functional Competence Development in Teachers: World Experience

Abstract: Teacher leadership is closely related to the level of professional competence. However, at the present development stage of the education system, this concept is not always fully understood and taken into account. The purpose of our research is to study the level of leadership of Russian school and university teachers, as well as to identify problems and suggest possible solutions. The survey involved 111 school teachers and university lecturers. The selection criterion is explained by the fact that leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
13
0
8
Order By: Relevance
“…In the context of professional development, training that teachers need are those that are suitable for their classrooms' needs and involve the teachers in the activities (An & Reigeluth, 2011;Bayar, 2014). Events of exchange experience allow teachers to learn new things and practice it (Berestova et al, 2020). Besides, the stakeholders need to be involved in the effort to develop teacher professional development (Whitworth & Chiu, 2015).…”
Section: Figure 3 Teachers' Participation In the Training Activitiesmentioning
confidence: 99%
“…In the context of professional development, training that teachers need are those that are suitable for their classrooms' needs and involve the teachers in the activities (An & Reigeluth, 2011;Bayar, 2014). Events of exchange experience allow teachers to learn new things and practice it (Berestova et al, 2020). Besides, the stakeholders need to be involved in the effort to develop teacher professional development (Whitworth & Chiu, 2015).…”
Section: Figure 3 Teachers' Participation In the Training Activitiesmentioning
confidence: 99%
“…Para el caso de las universidades y debido a que estas son organizaciones altamente complejas, el ejercicio de un liderazgo efectivo permite, además de motivar e inspirar a otros, articular una visión atractiva y otorgarle posicionamiento y seguridad a la institución, lo que ayudaría a su vez al logro de la excelencia institucional (Ganga-Contreras et al, 2018), es por esto que se reconoce la importancia de ejercer un liderazgo que garantice estrategias flexibles e integrales, destacando la capacidad de escuchar y respetar las ideas de todos los participantes en este proceso (estudiantes, profesores y otros stakeholders), con el fin de anticipar el cambio, estimular el diálogo, la cooperación, el conocimiento, la creatividad (Leal Filho et al, 2018), y conducir así a un clima de aprendizaje efectivo y procedimientos educativos eficaces (Daniëls et al, 2019). Es más, Berestova et al (2020) sostienen que el liderazgo docente promueve un crecimiento efectivo dentro del contexto educativo, ya que los académicos que se convierten en líderes contribuyen al desarrollo profesional efectivo de sus compañeros docentes, al crear comunidades líderes de especialistas que exploran y mejoran colectivamente las prácticas de enseñanza y aprendizaje, lo que tiene un efecto favorable en la calidad de la educación y el rendimiento de los estudiantes. De igual manera, los directivos que tienen una sólida comprensión de las prácticas efectivas de liderazgo, son gestores de una cultura y estructura orientada en el aprendizaje continuo, basada en las necesidades de los estudiantes y las capacidades de los académicos (Cawn et al, 2016), razón por la que Pedraja-Rejas et al (2018a) concluyen que desde un punto de vista conceptual, existe un probable vínculo entre los estilos de liderazgo y los tipos de cultura que prevalecen en las instituciones de educación superior.…”
Section: Liderazgo En La Educación Superiorunclassified
“…This suggests that teachers can significantly influence in policies as well as in the teaching practice, in a proactive, collective and collaborative way. Other authors agree in this concept (Berestova, Gayfullina, & Tikhomirov, 2020) by pointing that teacher leadership is based in the influence and interaction, rather than in power and authority; in professional development, communication, cooperation, the use of new ways of teaching (e-learning), and adapting the curricula to specific goals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On a research with elementary and higher education teachers (Berestova et al, 2020), the main results indicated that the participants: (a) are aware of the need for continuous professional development, which would increase their competence and thus, the education quality, (b) agree that educators should be proactive in implementing new teaching practices, (c) consider that most important personal qualities of leadership are the ability to make decisions, express their own ideas and proposing new ones, and (d) consider that most important professional qualities of leadership are the ability of team working and organizational skills. All these aspects can have a positive influence in the educational process and allow teachers to better understand the concept of teacher leadership and its importance in education.…”
Section: Theoretical Frameworkmentioning
confidence: 99%